1995
DOI: 10.1146/annurev.nu.15.070195.001025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glutaminase Activity and Glutamine Metabolism

Abstract: Glutamine is synthesized primarily in skeletal muscle, lungs, and adipose tissue. Plasma glutamine plays an important role as a carrier of nitrogen, carbon, and energy between organs and is used for hepatic urea synthesis, for renal ammoniagenesis, for gluconeogenesis in both liver and kidney, and as a major respiratory fuel for many cells. The catabolism of glutamine is initiated by either of two isoforms of the mitochondrial glutaminase. Liver-type glutaminase is expressed only in periportal hepatocytes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
367
1
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(391 citation statements)
references
References 0 publications
15
367
1
8
Order By: Relevance
“…Some of the enzymes in this pathway are present in a variety of cell types, while expression of other enzymes is highly restricted. Phosphate-dependent glutaminase, ornithine aminotransferase (OAT), argininosuccinate synthase (ASS), argininosuccinate lyase (ASL) and aspartate aminotransferase are widely distributed in animal tissues [42][43][44][45], whereas CPS I, ornithine carbamoyltransferase (OCT) and N-acetylglutamate Step 4 is a spontaneous, non-enzymic reaction. Glutamyl-γ-semialdehyde is in chemical equilibrium with P5C.…”
Section: Arginine Synthesismentioning
confidence: 99%
“…Some of the enzymes in this pathway are present in a variety of cell types, while expression of other enzymes is highly restricted. Phosphate-dependent glutaminase, ornithine aminotransferase (OAT), argininosuccinate synthase (ASS), argininosuccinate lyase (ASL) and aspartate aminotransferase are widely distributed in animal tissues [42][43][44][45], whereas CPS I, ornithine carbamoyltransferase (OCT) and N-acetylglutamate Step 4 is a spontaneous, non-enzymic reaction. Glutamyl-γ-semialdehyde is in chemical equilibrium with P5C.…”
Section: Arginine Synthesismentioning
confidence: 99%
“…Keywords glutamine; glutamine synthetase; skeletal muscle; liver; adipocyte; insulin; glucocorticoids Glutamine is the most abundant free α amino acid in most mammalian species. The plasma glutamine pool is turning over very rapidly since it plays important roles in the interorgan transport of carbon, nitrogen and energy [1]. Although present in the diet, most ingested glutamine is metabolized by the small intestinal mucosa and thus the large body pool of glutamine is synthesized de novo [2].…”
mentioning
confidence: 99%
“…These changes in tubule function are associated with changes in the activities of a number of proteins, including the apical membrane Na ϩ /H ϩ antiporter (7), glutaminase and glutamate dehydrogenase (8), and phosphoenolpyruvate carboxykinase (9), which may affect intracellular substrate availability for protein turnover, amino acid metabolism and/or transport, and gluconeogenesis. It has been shown that in tubule epithelial cells, the associated increase in ammonia production, rather than the acidosis per se, is responsible for favoring tubular hypertrophy (10 -12).…”
mentioning
confidence: 99%